IDENTIFIKASI BAKTERI Escherichia Coli DAN COLIFORM PADA DEPOT AIR MINUM ISI ULANG KECAMATAN TRUCUK BOJONEGORO - Amalia, Isna Nur; Rahmawati, Laily Agustina; Elvania, Nindy Calista (Universitas Pakuan, 2025)
Water is a very basic need for human life on earth. At this time, water is a problem that needs careful attention. Drinking water is water that is consumed directly by humans through a processing process or processing stages that meet health requirements. The busier human activities are, the more people tend to choose a more practical way with relatively low costs in meeting drinking water needs. The fulfillment of drinking water needs is highly dependent on the coverage of drinking water services and sanitation conditions in the community. This study aims to determine the level of contamination of Escherichia coli and coliform bacteria in refill drinking water and the feasibility of refill drinking water depots in Trucuk District, Bojonegoro Regency. The method used in this study is descriptive with a quantitative approach. The results of the study from 4 samples, namely AB, DAM 1, DAM 2, and DAM 3. 3 samples including AB, DAM 1, and DAM 3 were positive for containing Escherichia coli and coliform bacteria. Refill drinking water samples and raw water do not meet the requirements in accordance with the quality standards in the Regulation of the Minister of Health of the Republic of Indonesia No. 492 of 2010